PERTANGGUNG JAWABAN PIDANA TERHADAP IBU YANG MELAKUKAN TRAFFICKING PADA ANAKNYA (STUDI KASUS JLN. BHAYANGAKARA NO. 385) - Muhammad Bagus Anshary Sinaga; Muhammad Rizal (Jurnal Hukum Lex Generalis, 2025)
In the era of globalization, the development of criminal acts continues to increase. Human trafficking is a form of modern slavery, even a mother as a parent is willing to sell her child because of material needs. This study aims to analyze the criminal liability for mothers who commit child trafficking against their children, as well as to examine the factors behind the act. The results of the study indicate that mothers involved in child trafficking can be charged with the provisions of Law Number 21 of 2007 concerning the Eradication of the Crime of Human Trafficking, with a heavier criminal threat if carried out against children. This study uses an empirical juridical type, namely field research, using a qualitative approach, namely methods and techniques based on the author's curiosity about juridical symptoms or how to find truth in knowledge. Keywords: Criminal Liability, Child Trafficking, Children’s Rights